2015
DOI: 10.4314/ejhs.v25i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic urinary tract infection among pregnant women receiving ante-natal care in a traditional birth home in Benin city, Nigeria

Abstract: BACKGROUND: A good proportion of pregnant women patronize traditional birth homes in Nigeria for ante-natal care. This study aimed at determining the prevalence, risk factors, and susceptibility profile of etiologic agents of urinary tract infection among ante-natal attendees in a traditional birth home in Benin City, Nigeria. METHODS: Clean-catch urine was collected from 220 pregnant women attending a traditional birth home in Benin City, Nigeria. Urine samples were processed, and microbial isolates identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
3
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 14 publications
9
48
3
7
Order By: Relevance
“…Okonko et al (16) observed an incidence rate of 47.5% among pregnant women in Oluyoro Catholic Hospital, Ibadan, Nigeria while Onifade et al (19) obtained an incidence rate of 58% in a similar study among pregnant women in Ondo, Nigeria. Others who also worked among pregnant women in Nigeria include Oladeinde et al (18) with incidence rate of 55.0% and Lawani et al (20) with incident rate of 25.3%. The high incidence rate obtained in this study could be attributed to the environmental conditions where subjects reside.…”
Section: Resultsmentioning
confidence: 99%
“…Okonko et al (16) observed an incidence rate of 47.5% among pregnant women in Oluyoro Catholic Hospital, Ibadan, Nigeria while Onifade et al (19) obtained an incidence rate of 58% in a similar study among pregnant women in Ondo, Nigeria. Others who also worked among pregnant women in Nigeria include Oladeinde et al (18) with incidence rate of 55.0% and Lawani et al (20) with incident rate of 25.3%. The high incidence rate obtained in this study could be attributed to the environmental conditions where subjects reside.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence rates of 6.1-10.9% have been reported from Iran, 7.3% in Ghana and 13% -21% from Tanzania between 2009 and 2010 (9,21). A higher rate (55%) was reported from Nigeria (22). One previous study indicated that the prevalence rate might be even higher in resources-limited countries, particularly among persons of lower socioeconomic status (23).…”
Section: Discussionmentioning
confidence: 97%
“…This finding is comparable with those reported in Adama, Ethiopia (37.3%), [7] and Nigeria (37.8%). [9] In pregnant women, progesterone relaxes ureteric smooth muscle which causes dilatation of ureters which additionally aggravates as a result of pressure from the enlarging uterus. All of these factors bring urinary stasis, dysfunctional ureteric valves and vesico-ureteral reflux, which assists bacterial colonization and rising infection.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly implicated bacteria responsible for ASB in pregnant women are Escherichia coli, Proteus spp., Klebsiella spp., Pseudomonas spp., Enterococcus spp., Staphylococcus aureus, and coagulase-negative Staphylococci. [6][7][8][9][10] Escherichia coli is the most predominant bacteria that cause asymptomatic UTI among pregnant women. [11,12] ASB due to Streptococcus agalactiae (group B Streptococcus) has been associated with adverse obstetric outcomes.…”
Section: Introductionmentioning
confidence: 99%